Thermoregulation in rabbits - Fayez I.; Marai M.; Alnaimy A.; Habeeb M. (Rabbit production in hot climates, 1994)
Temperature of 21 degrees centigrade is the comfort zone in rabbits. When the animals are exposed to higher or lower temperature, the heat dissipation or heat production must be carried out to maintain its body temperature. Thermoregulation mechanism is conducted by different means. Respiration, the nasal mucose and the ear are the important heat dissipation pathways in rabbits.
1. International Conference of rabbit production in hot climates, 1994/09/06-08, Cairo (Egypt)